AFGHANISTAN: SETTLEMENT STAGES AND AFTERMATH OF THE POST-CONFLICT SITUATION - AKMALOV, Shoislam (CENTRAL ASIA AND THE CAUCASUS, 2006)
Afghanistan is living through a protracted stage of the so-called postwar settlement process and the growing threat of further deterioration. It has become obvious that the Unit-ed States and its allies are unable to maintain stability in Afghanistan in the context of the mounting political tension around Iran and Pakistan. An analysis of the current situation in Afghanistan must inevitably take into account two key events: President George W. Bush’s visit to Afghanistan and the London Donor Conference on Afghanistan. These events have determined the course of Washington’s and the world community’s Afghan policy and symbolize its evolution.